Choice of optimal exchange rate system For the Republic of Croatia - Dražen Koški (Ekonomski Vjesnik, 2008)
The aim of research whose results are presented in this article was to choose the optimal system of exchange rate for the Republic of Croatia, of course before its accession to EU. The analyzed exchange rate systems here range from free-floating exchange rate to system without domestic currency in circulation. Naturally, the classification of International Monetary Fond is included in it. After that, the comparison of basic economic advantages and disadvantages of the fixed exchange rate in relation to floating exchange rate were carried out. Although the question is about the extreme systems, disregarding the system without domestic currency in circulation, their comparison makes possible completely satisfactory basis for the right conclusions on the choice of optimal exchange rate system for the Republic of Croatia. Considering its economic particularities, the system of managed-floating exchange rate without proclaimed exchange direction in advance is certainly optimal for the Republic of Croatia. Namely, within the framework of this system the limited floating exchange rates decrease the foreign exchange risk allowing to monetary authorities, at least partly, the independent monetary policy